Wartości kulturowe a rola współczesnego menedżera - Stańczyk, Sylwia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Globalization, connected with increasing uncertainty, goes to some tendency in organizational culture. The purpose of this paper is to show an important change of manager's role in the face of these changing values. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 413-419